Air-Stable Li6CoO4@Li5FeO4 Pre-Lithiation Reagent in Cathode Enabling High Performance Lithium-Ion Batteries. Issue 8 (9th August 2021) - Li, Jie; Zhu, Bin; Li, Shihao; Wang, Dapeng; Zhang, Wei; Xie, Yangyang; Fang, Jing; Hong, Bo; Lai, Yanqing; Zhang, Zhian
Abstract : Li5 FeO4, as a high-capacity built-in pre-lithiation reagent, has attracted wide interest due to its attractive characteristics, such as extremely higher capacity and energy density, low cost, and environmental friendliness. However, the preparation technology of high-stability Li5 FeO4 remains a great challenge. Here, we report a highly air-stable Li5 FeO4 cathode pre-lithiation reagent by the solid-phase method. The Li5 FeO4 is coated with Li6 CoO4 (Li6 CoO4 @Li5 FeO4, referred to as LCO@LFO), which can effectively improve the stability of Li5 FeO4 materials under ambient atmosphere and significantly enhance the electrochemical performance. The material possesses an initial charge capacity of 518.8mAh g −1 when charged to 4.5 V and exhibits good air-filled capacity retention. Besides, the LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) full-cell with 5 wt% LCO@LFO additive has an initial discharging capacity of 205 mAh g −1 in the charge and discharge interval of 2.0 V–4.5 V (vs Li + /Li), respectively, higher than the initial discharging capacity of 166.5 mAh g −1 of pure NCM811. The reversible specific capacity of the NCM811 with LCO@LFO cathode in the full cell can be increased by 8.8%, which is equivalent to a 14.35% increase in energy density. Our research report opens a door for the commercial application of LCO@LFO, a high-stability cathode composite pre-lithiation reagent.